Nutrition, rumen health and inflammation in the transition period and their role on overall health and fertility in dairy cows. (December 2015) - Zebeli, Q.; Ghareeb, K.; Humer, E.; Metzler-Zebeli, B.U.; Besenfelder, U.
Abstract: Transition is a stressful period and critical for the entire cow's productive lifespan and reproduction. Optimal feeding management during transition period enables smooth metabolic adaptation to the initiation of lactation. Major nutritional challenge during this period is the urgent need to counteract the drastic deficits in energy and nutrients of the early-lactating cow. This is primarily done by inclusion of large amounts of concentrates in the diet during early lactation, causing major dietary imbalances with utmost importance for rumen health. Proper feeding management targeting rumen health in the transition period improves nutrient degradation and the net supply with energy and key nutrients of the host while preventing systemic disturbances and inflammation, events which are instrumental for cow's overall health and reproductive performance. The review provides insights into the role of, and gives practical hints regarding diet balancing efforts and feeding management strategies targeting rumen health and systemic inflammation during the periparturient period with the aim to enhance cow health and fertility. Highlights: Article suggests rumen-health targeted feeding management in transition cows. Rumen health during transition period is critical for cow's health and fertility. Promotion of rumen health is a proactive strategy to enhance fertility in cows. Article provides practical examples of dietary optimization in transition period. Article identifies research gaps needing to be addressed by further research.